The Kenya Rural Enterprise Program : Directing Credit to Low-Income Groups - Pederson, Glenn D.; Kiiru, Washington K. (World Bank, Washington, DC, 2012)
The lack of credit facilities in Kenya's rural areas is a significant obstacle to building a sustainable rural financial market. A recent estimate placed the gap between the level of credit supplied and the effective demand for credit at some Ksh. 57 billion. The Government of Kenya has, since the early 1990s, shown an interest in the development of small-scale and micro-enterprises. The Kenya Rural Enterprise Program (K-REP) was established in 1984 as an intermediary Non Government Organization (NGO), providing credit for on lending and technical assistance to other NGOs. To promote growth and generate employment in the micro-enterprise sector, K-REP lends to clients who would otherwise find it extremely difficult to access credit from commercial banks and other formal financial institutions. Its operations are currently concentrated in Nairobi, Nyeri, Eldoret and Embu. Kenya Rural Enterprise Program: case study of a micro-finance scheme documents K-REP's innovations and performance, and provides some insight on how to improve micro-finance programs.